Development and discontent in tribal India - Sisodia, Yatindra Singh; Dalapati, Tapas Kumar (Jaipur: Rawat Publications, 2015)
Contributed papers presented at a seminar titled Development and Discontent in Tribal India held at Madhya Pradesh Institute of Social Science Research, Ujjain in the year 2012.
Includes bibliographical references and index.
Keywords: INDIA -- SCHEDULED TRIBES -- ECONOMIC CONDITIONS; INDIA -- SCHEDULED TRIBES -- GOVERNMENT POLICY